Evaluation of a Multidisciplinary Antimicrobial Stewardship Program in a Saudi Critical Care Unit: A Quasi-Experimental Study - Haseeb, Abdul; Faidah, Hani Saleh; Al-Gethamy, Manal; Iqbal, Muhammad Shahid; Barnawi, Abrar Mohammed; Elahe, Shuruq S.; Bukhari, Duha Nabeel; Noor Al-Sulaimani, Turki Mohammad; Fadaaq, Mohammad; Alghamdi, Saad; Almalki, Waleed Hassan; Saleem, Zikria; et al. (Frontiers in Pharmacology, 2021)
Background: Antimicrobial stewardship programs (ASPs) are collaborative efforts to optimize antimicrobial use in healthcare institutions through evidence-based quality improvement strategies. With regard to critically ill patients, appropriate antimicrobial usage is of significance, and any delay in therapy increases their risk of mortality. Therefore, the implementation of structured multidisciplinary ASPs in critical care settings is of the utmost importance to promote the judicious use of antimicrobials. Methods: This quasi-experimental study evaluating a multidisciplinary ASP in a 20-bed critical care setting was conducted from January 1, 2016 to July 31, 2017. Outcomes were compared nine months before and after ASP implementation. The national antimicrobial stewardship toolkit by Ministry of health was reviewed and the hospital antibiotic prescribing policy was accordingly modified. The antimicrobial stewardship algorithm (Start Smart and Then Focus) and an ASP toolkit were distributed to all intensive care unit staff. Prospective audit and feedback, in addition to prescribing forms for common infectious diseases and education, were the primary antimicrobial strategies. Results: We found that the mean total monthly antimicrobial consumption measured as defined daily dose per 100 bed days was reduced by 25% (742.86 vs. 555.33; p = 0.110) compared to 7% in the control condition (tracer medications) (35.35 vs. 38.10; p = 0.735). Interestingly, there was a negative impact on cost in the post-intervention phase. Interestingly, the use of intravenous ceftriaxone measured as defined daily dose per 100 bed days was decreased by 82% (94.32 vs. 16.68; p = 0.008), whereas oral levofloxacin use was increased by 84% (26.75 vs. 172.29; p = 0.008) in the intensive care unit. Conclusion: Overall, involvement of higher administration in multidisciplinary ASP committees, daily audit and feedback by clinical pharmacists and physicians with infectious disease training, continuous educational activities about antimicrobial use and resistance, use of local antimicrobial prescribing guidelines based on up-to-date antibiogram, and support from the intensive care team can optimize antibiotic use in Saudi healthcare institutions.